1393 Impact of occupational stress in italian offshore oil installation workers and cytokines homeostasis. (24th April 2018) - Di Giampaolo, L; Costantini, E; D'Angelo, C; Frassanito, F; Di Gioacchino, M; Di Nicola, M; Reale, M
Abstract : Introduction: Environmental, behavioural and psychological stimuli can activate inflammation. Psychosocial factors such as work demands and decision latitude, social support, and psychological distress, play important roles in the development of inflammatory status. We conducted a study on occupational stress and its influence on cytokines homeostasis in Italian offshore oil installation workers. Methods: Enrolled workers from an offshore oil company were divided into two groups, which took rotations of four weeks to work on the platforms at sea. The onshore and offshore groups were broadly the same in terms of their ranking, work experience, age, and distribution of job categories. All subjects complete a self- administered questionnaire collecting information on socio-demographic characteristics, occupational stress, sleep disorders, and past injuries. The salivary cortisol and serum cytokines levels were measured by ELISA, cytokines gene expression was evaluated by Real-time PCR. Results: Salivary cortisol concentrations were significantly increased confirming the effectiveness of occupational stress. In fact, in our workers, cortisol level was directly correlated to job insecurity, State-Trait Anxiety (STAI-1), shift work and inversely proportional to sleep quality. In addition, we observed a direct correlation also between BMI and cortisol level. A significant increase of TNFa and a weak elevation of IL-10 level were observed in the offshore group. To examine whether changes in cytokines levels were due to changes in cell type composition, a reduction of ratio between lymphocyte percentages and neutrophils percentages (Ly/Ne%) were observed. Spontaneous expression of IL-1b, TNFa and IL-10 were higher in offshore respect to onshore workers. The increase in all PHA-induced cytokine release was significantly higher in the offshore workers. Only TNFa was significantly higher in LPS-stimulated PBMC of offshore workers. Conclusion: Taken together, the current study revealed that occupational stress not only activates neuroendocrine stress systems, but also influence cytokines homeostasis.